Law Students’ Awareness of University Graduate Attributes - Smith, Leigh; Do, Christina (2018)
Despite the importance of university graduate attributes, and the emphasis that is placed on them, it is unclear whether students fully comprehend what university graduate attributes are, why they exist, and the specific graduate attribute(s) of the institution at which they are enrolled. This paper explores university graduate attributes from the perspective of students. While the paper provides an overview of the concept of university graduate attributes, the focus of the paper is on the examination of the data collected from a pilot project conducted at Curtin Law School in 2018, which explored law students’ awareness of the Curtin Graduate Attributes. This paper also reflects on how academic staff can help enhance students’ awareness and acquisition of university graduate attributes.